Explanation:
Let's call the angle whose tangent is 3 as angle θ. The tangent of angle θ is given as 3.
Now, let's find the tangent of the other acute angle, which we'll call angle α.
In a right triangle, the sum of the angles is 90 degrees. So, θ + α = 90 degrees.
We know that the tangent of θ is 3, which means:
tan(θ) = 3
Now, we can find the tangent of α using the tangent addition formula:
tan(θ + α) = tan(90 degrees)
Using the tangent addition formula:
tan(θ + α) = (tan(θ) + tan(α)) / (1 - tan(θ) * tan(α))
We know that tan(θ) is 3:
3 + tan(α) / (1 - 3 * tan(α))
Now, we can solve for tan(α):
3 + tan(α) = 0
tan(α) = -3
So, the tangent of the other acute angle α is -3.
Among the given options, the correct one is:
O -√3 13